Akuntansi sebagai Realitas Konstruksi: Akuntansi (Informasi) dan Akuntabilitas dalam Praktik Bisnis dari Perspektif "Khalifatullah Fil Ardhi" - Suyudi, Muhammad (Jurnal Aplikasi Manajemen, 2008)
This paper tries to see the concept of individual accountability where is discussed based on accounting background in a private business at ekonomi komando to the market economic. The face of accountability concept, is performed as interpretation and translation from institutional structure with rutionality. Many literature performs the change of view about accountability supporting institutional process, to form business as market economic actor, where is fighter between different rational view about market economic, social accountability, and production orientation. Research method, this research constitute literature investigation in qualitative method. This process used to hermeunitic or interpretivism Category in accounting. The result, perform various method where is related with a new method of study about business and it performance between market economic condition. I have challenge that accounting can be calculated with the method how to handle the consequences of individual actionin business community. This critical point is to relate accounting and accountability and the existence of business as organization in Khalifatullah Fil-Ardh perspective.